Photonic Crystals: High‐Q 2D Lithium Niobate Photonic Crystal Slab Nanoresonators (Laser Photonics Rev. 13(5)/2019). Issue 5 (8th May 2019) - Li, Mingxiao; Liang, Hanxiao; Luo, Rui; He, Yang; Lin, Qiang
Abstract : In article number1800228, Qiang Lin and co‐workers demonstrate high‐Q two‐dimensional lithium niobate photonic‐crystal‐slab nanoresonators to enhance light–matter interaction on the nanoscale. With the specific polarization characteristics, the devices enable peculiar nonlinear optical properties, as well as strong orientation‐dependent harmonic generation to be revealed.